Opioid overdose and naloxone administration knowledge and perceived competency in a probability sample of Indiana urban communities with large Black populations - Shin Hyung Lee; Jon Agley; Vatsla Sharma; Francesca Williamson; Pengyue Zhang; Dong-Chul Seo (PLoS ONE, 2025)
Background Opioid overdose deaths pose a serious public health concern in the United States, with disproportionately higher rates of increase among Black Americans despite expanded naloxone access. Improving community knowledge and confidence in naloxone use may be critical to reducing these disparities. Objective This study assessed individual- and community-level factors associated with knowledge and perceived competency in managing opioid overdose and administering naloxone among urban Indiana residents. Methods A probability-based household survey was conducted between March to May 2023 across eight Indiana zip code areas (N = 772) with high (> 40%) proportions of Black residents. Multilevel modeling was used to examine individual- and community-level factors associated with opioid overdose knowledge and perceived competency, using adapted items from the Opioid Overdose Knowledge Scale (OOKS) and Opioid Overdose Attitudes Scale (OOAS). Results Race, sex, household income, education, time lived in the community, and history of opioid overdose significantly predicted knowledge scores. White participants scored higher (mean 6.65) than Black participants (5.70) ( p < 0.001). A significant cross-level interaction was found, with Black residents living in high-poverty areas scoring lower than White counterparts (β = 1.06, p = 0.039). In contrast, perceived competency was primarily associated with age and personal history of overdose. Conclusions Racial and socioeconomic disparities persist in opioid overdose knowledge, particularly among Black residents in low-income communities. Tailored, culturally responsive education efforts, especially by trusted community members, may help improve overdose response readiness.